Daya Tarik Linguistik dalam Promosi Kuliner: Analisis Pragmatik Multimodal pada Penamaan Menu Unik - Aditya Pratama; Isnaniah; Aisha Nadya; Aziz Fauzi; Aksara Ciptaning Tahta; Cantika Sari Wahyuni (Paedagogie, 2026)
In the increasingly competitive culinary industry, promotional strategies focus not only on product quality but also on the use of language as a means of persuasive communication. Unique menu naming is one linguistic strategy that can build an image, attract attention, and influence consumer decisions. This study aims to analyze the linguistic appeal in culinary promotions through menu naming using a multimodal pragmatic approach, which focuses on the function of speech acts and the role of multimodal elements in constructing meaning. This study uses a qualitative approach with a descriptive-exploratory design. Data in the form of menu names obtained from Instagram social media through documentation and screenshot techniques, then analyzed using speech act theory and a multimodal approach. The results of the study indicate five main categories of menu naming: the use of foreign languages, local languages, a combination of both, extreme terms, and power terms. Pragmatically, the dominant function of speech acts is directives that implicitly encourage consumption actions. Multimodally, meaning and appeal are built through the integration of text with visual elements such as color, typography, and illustrations. Thus, menu naming is an effective persuasive communication strategy through the synergy of linguistic and multimodal aspects in influencing consumer perceptions and decisions.